2016
DOI: 10.1130/b31318.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of autochthonous versus detrital micrite in depositional geometries of Middle Triassic carbonate platform systems

Abstract: Middle Triassic platforms (Formazione di Contrin, Upper Anisian) in the Italian Dolomites, southern Alps, record large changes in carbonate production and depositional geometry. The changes include variation in the abundance of detrital micrite, i.e., allochthonous calcareous mud, relative to the autochthonous micrite, which formed in situ and was syndepositionally lithified. Carbonate factory dynamics controlled the geometry of the clinostratified slope units and were probably associated with changes in oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 138 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…Micrite matrix in marine limestones is commonly believed to record at least some geochemical properties of the ocean water from which it precipitated, and is a widely used archive for paleoclimate and paleoenvironmental reconstructions (Bartolini et al., 1999; Coimbra et al., 2009; Y. Gao et al., 2018; Guido et al., 2016; Kasemann et al., 2005; Martin et al., 2012; Rais et al., 2007). However, micrite can be chemically altered through recrystallization during burial and extensive recrystallization has been suggested to have occurred on Paleozoic carbonates (Bennett et al., 2018; Cummins et al., 2014; G. Gao & Land, 1991; Joachimski et al., 2004; Land & Lynch, 1996; Ryb & Eiler, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Micrite matrix in marine limestones is commonly believed to record at least some geochemical properties of the ocean water from which it precipitated, and is a widely used archive for paleoclimate and paleoenvironmental reconstructions (Bartolini et al., 1999; Coimbra et al., 2009; Y. Gao et al., 2018; Guido et al., 2016; Kasemann et al., 2005; Martin et al., 2012; Rais et al., 2007). However, micrite can be chemically altered through recrystallization during burial and extensive recrystallization has been suggested to have occurred on Paleozoic carbonates (Bennett et al., 2018; Cummins et al., 2014; G. Gao & Land, 1991; Joachimski et al., 2004; Land & Lynch, 1996; Ryb & Eiler, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable microbialites in the Pleistocene-Holocene reef at Tahiti contain lipid biomarkers indicating a bacterial community dominated by sulphate-reducing bacteria (SRB) that degraded organic matter (Heindel et al 2010(Heindel et al , 2012. Similarly, the involvement of SRB in autochthonous micrite precipitation was recognized in cryptic bioconstructions of recent (Guido et al 2012(Guido et al , 2013(Guido et al , 2016(Guido et al , 2017a and Pleistocene (Guido et al 2017b) submarine caves. Kershaw et al (2012) identified several microbialitic facies developed after the Permian extinction in the low-latitude Tethys Ocean, with similar characteristics to those of 'La Cerchiara' .…”
Section: A B D Cmentioning
confidence: 99%
“…One of the most remarkable examples of this importance is the Dolomites depositional system (eastern Alps, north Italy). There, from Anisian to Carnian times, low-relief terrigenous-carbonate ramps, rich in loose micritic mud, evolved into isolated high-relief carbonate pinnacles, in which syndepositional cements, together with autochthonous micrite, played a key role in the carbonate production and in the stabilization of the depositional geometries (Bechstädt & Brandner 1970;Biddle 1981;Brandner & Resch 1981;Gaetani et al 1981;Bosellini 1984;Brandner et al 1991Brandner et al , 2007Brandner et al , 2012Harris 1993Harris , 1994Blendinger 1994Blendinger , 1996Keim & Schlager 1999Russo 2005; Seeling et al 2005;Stefani et al 2010;Brandner & Keim 2011;Marangon et al 2011;SĂĄnchez-Beristain & Reitner 2012Guido et al 2016Guido et al , 2018Guido et al , 2019a. Russo et al (2000) recognized the role and the abundance of primary cements in the carbonate facies of the Dolomites, where they represent the major constituent of the Triassic Marmolada platform, forming more than 50% of the rock volume.…”
mentioning
confidence: 99%
“…This feature arguably limited a drop in seawater pH in the platform-top domain, allowing for significant carbonate production as documented by microencruster facies expansion found in Istria and in other locations. Recent international research initiatives such as BIOACID have documented the fact that most marine metazoans tolerate one stressor to some degree (see, for example, bivalves in Hahn et al, 2012) provided that sufficient food is available. But if, for example, high temperatures plus low seawater pH act in parallel, these organisms reach their tolerance limits.…”
Section: Principles Of Recent Coastal Hypoxia and Tentative Applicabimentioning
confidence: 99%